2020
DOI: 10.1088/1402-4896/ab560c
|View full text |Cite
|
Sign up to set email alerts
|

Role of non-integer and integer order differentiations on the relaxation phenomena of viscoelastic fluid

Abstract: The dynamics of elastic, anelastic responses and thermoelastic relaxation mechanism can be exhibited by the viscoelastic materials. This manuscript aims to present the analytical study of viscoelastic fluid based on non-integer and integer order differentiations. The mathematical modeling of viscoelastic fluid has been established in terms of partial differential equations for the velocity field corresponding to the shear stress subject to the fractional approaches. The partial differential equations govern th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 64 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Finite Fourier sine transform, Laplace, and fractional techniques have been utilized to the governing equations for exhibiting typical and rheological properties of the problem. Although the studies on heat and transfer analysis can be continue yet the relevant studies can be observed therein in categorical format as heat transfer via analytical approaches [16][17][18][19][20][21][22][23], heat transfer via numerical approaches [24][25][26][27][28][29], heat transfer via fractional calculus approaches [30][31][32][33], and heat transfer via multi-dimensional approaches [34][35][36][37]. Motivating by the above consideration, the main theme of this manuscript is to have the significance of convective heating and variable heat source on Azimuthal oscillatory MHD convective flows developed in a cylindrical Darcy-Forchheimer porous medium filled by a radiating second-grade fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Finite Fourier sine transform, Laplace, and fractional techniques have been utilized to the governing equations for exhibiting typical and rheological properties of the problem. Although the studies on heat and transfer analysis can be continue yet the relevant studies can be observed therein in categorical format as heat transfer via analytical approaches [16][17][18][19][20][21][22][23], heat transfer via numerical approaches [24][25][26][27][28][29], heat transfer via fractional calculus approaches [30][31][32][33], and heat transfer via multi-dimensional approaches [34][35][36][37]. Motivating by the above consideration, the main theme of this manuscript is to have the significance of convective heating and variable heat source on Azimuthal oscillatory MHD convective flows developed in a cylindrical Darcy-Forchheimer porous medium filled by a radiating second-grade fluid.…”
Section: Introductionmentioning
confidence: 99%
“…is new AB derivative is nonsingular and has nonlocal kernel and possesses the long memory due to the existence of Mittag-Lefler kernel which is the generalization of the exponential kernel. is new AB fractional derivative in Caputo sense of order α > 0 is defined as follows [47,48]:…”
Section: Problem Formulationmentioning
confidence: 99%
“…Viscoelasticity has important implications due to the characterization of viscoelastic parameters (relaxation and retardation phenomenon), elastic shearing strain, thermal relaxation, time‐dependent anelastic aspect, and other rheological properties 1‐3 . In this regard, Qi and Jin 4 suggested constitutive relationship of a viscoelastic material based on fractional derivative on the basis of simple harmonic motion or impulsively rotating motion of the outer cylinder.…”
Section: Introductionmentioning
confidence: 99%